(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Linguists say in different languages tend to encode the spatial position of objects in terms of the "sit-stand-lie". According to scientists, this trend indicates that the relevant verb structure is the basic and most frequently used. In this article we consider the features of the use of the verb sit from names of animate nonhuman objects.